Development and Irrigation of Mirzachul Lands - Davletov Rasulbek Djumabayevich (International Journal of Advanced Science and Technology, 2020)
The article examines the development of Mirzachul gray lands in the territory of the Republic of Uzbekistan, the organization of water supply in the Soviet era, the work carried out in the period 1950-1970 and their consequences.